Effectiveness of school managers’ technology integration in senior high school management in Ghana - Gabriel-Wettey, Francis Kwesi Nsakwa; Mintah, Josephine Adjoa; Asomah, Richard Kyere; Abonyi, Usman Kojo (Papanda Publisher, 2025)
This study assessed the effectiveness of school managers’ technology integration in school management in senior high school (SHS), Ghana. Exploratory case study design was employed. A multi-stage sampling technique was used to select ten managers from some selected SHSs in Ghana. Data was analyzed thematically, and results were reported through a narrative that incorporated themes and subthemes. The study revealed that school managers extensively use ICT tools across five key areas: communication and collaboration, teaching and learning support, data management and record-keeping, financial and management processes, and library and information management. However, the study revealed that effective use of these tools depends on teacher competency, institutional policies, and access to technology. Also, the results showed that technology integration in school management had significantly improved management efficiency, teaching-learning, financial management, and communication. To this end, time-saving and reduced paperwork, accurate data records and informed decision-making, effective communication, reduced workforce and increased efficiency, and precise financial records were perceived as the five key themes that characterize the introduction of ICT in school management. Finally, challenges of infrastructure/resource limitations, internet connectivity, financial constraints, lack of technical support, user-related challenges, and software/system compatibility were identified as barriers to management efficiency and teaching-learning outcomes in the study.